2017
DOI: 10.1108/intr-07-2016-0223
|View full text |Cite
|
Sign up to set email alerts
|

Twitter as customer’s eWOM: an empirical study on their impact on firm financial performance

Abstract: Purpose -The purpose of this paper is to investigate the relationship between customer's electronic word-of-mouth (eWOM) regarding their direct service experiences with firms and these firms' company value. The authors drew on the marketing-finance interface research approach to demonstrate how interactive social media adopted by individual customer relate to important firms' financial performances. Design/methodology/approach -The authors used seven American airline companies' customers' tweets collected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 77 publications
2
43
0
Order By: Relevance
“…These sources can initiate brand suggestions and recommendations for their close social circle. A study verified that the sharing of UGC on social media platforms is based on culture, race, gender, and social context (Xun & Guo, 2017). Previous studies have also supported the precept that those individuals who are physical known, experienced and credible, such as family members or close friends, can positively influence purchase decisions for various brands (Bacile, Wolter, Allen, & Xu, 2018; Djafarova & Rushworth, 2017; Farzin & Fattahi, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These sources can initiate brand suggestions and recommendations for their close social circle. A study verified that the sharing of UGC on social media platforms is based on culture, race, gender, and social context (Xun & Guo, 2017). Previous studies have also supported the precept that those individuals who are physical known, experienced and credible, such as family members or close friends, can positively influence purchase decisions for various brands (Bacile, Wolter, Allen, & Xu, 2018; Djafarova & Rushworth, 2017; Farzin & Fattahi, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Estrella‐Ramón and Ellis‐Chadwick (2017) indicated that negative UGC damages brand engagement and has an impact on the level of trust in brands. Many other studies indicated that negative comments are trusted by SMUs and these negative comments also create reliability of UGC in a consumer's mind (Goh, Heng, & Lin, 2013; Haigh & Wigley, 2015; Jin & Phua, 2016; Xun & Guo, 2017). The limitations of such studies are that they do not focus sufficiently on the context of social influence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate reporting practices have been brought to the public sector, suggesting that there might be parties interested in these numbers and in the financial situation, although this so-called new public management trend with private sector accounting disclosure and practices does not always suit the conditions of the public sector (Lapsley, 2009). Recently the use of social media and information technology has brought about changes in how we obtain organization-specific information (see Quattrone, 2016;Xun and Guo, 2017). Media attention may affect organizational perceptions (Johnsen et al, 2019), and especially the negative tone of social media discussion tends to have a link to decreasing performance and stock prices (Xun and Guo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated rating refers to the rating that reflects former consumers' overall evaluation of a service provider, while individual reviews usually include the rating that a single consumer gives to a service provider, aligned with descriptive texts and, sometimes, images. These two types of eWOM information in the context of review sites are thought to influence both consumers' decision making and business growth (Luca, 2011;Xun and Guo, 2017). eWOM researchers recognise the significance of understanding how different types of eWOM information, specifically AR and IR, on review sites, and the valence congruence/incongruence between them, influence consumer perception and behaviour at different stages of the decisionmaking process, particularly in service settings (Aggarwal and Singh, 2013;Chen et al, 2015;Qiu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%